2012
DOI: 10.1038/onc.2012.64
|View full text |Cite
|
Sign up to set email alerts
|

Low dose IR-induced IGF-1-sCLU expression: a p53-repressed expression cascade that interferes with TGFβ1 signaling to confer a pro-survival bystander effect

Abstract: Inadvertent mammalian tissue exposures to low doses of ionizing radiation (IR) after radiation accidents, remediation of radioactive-contaminated areas, space travel, or a dirty bomb represents an interesting trauma to an organism. Possible low dose IR-induced bystander effects could impact our evaluation of human health effects, since cells within tissue are not equally damaged after doses of IR ≤10 cGy. To understand tissue responses after low IR doses, we generated a reporter system using the human clusteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…1b), reaching maximal death inhibitory activity at 100 J/m 2 . These results are consistent with published reports that reduced apoptosis or increased survival of unexposed cells is one of the endpoints of RIBE 3,79 .…”
supporting
confidence: 93%
“…1b), reaching maximal death inhibitory activity at 100 J/m 2 . These results are consistent with published reports that reduced apoptosis or increased survival of unexposed cells is one of the endpoints of RIBE 3,79 .…”
supporting
confidence: 93%
“…Although these studies added to previous findings suggesting a tumor-suppressing effect of CLU, CLU expression levels were positively correlated with disease progression in the majority of reported studies [16]. More recently, it was found that AKT exerted its cytoprotective role in prostate tumor cells via the induction of CLU [70], as well as that low-dose ionizing radiation-induced IGF-1 mediates CLU expression that interferes with TGFβ1 signaling to confer a prosurvival bystander effect [71]. Moreover, in prostate cancer cells, CLU mediated TGF-β-induced epithelial-mesenchymal transition and metastasis via Twist1 [72], while transcriptome profiling in a TGF-β-induced epithelial-mesenchymal transition model revealed extracellular CLU as a target for therapeutic antibodies [73].…”
Section: Functional Implication Of Clu In Ageing and Age-related Disementioning
confidence: 55%
“…In addition to ionizing radiation (Hildesheim et al, 2002;Klokov et al, 2012;Rashi-Elkeles et al, 2011), p53 activity can also be induced by oncogenic stress (Feng et al, 2006;Yan et al, 2005), oxidative stress (Achanta and Huang, 2004;Sinthupibulyakit et al, 2010), signaling cytokines (Doman et al, 1999;Kim et al, 2005), changes in temperature Michalovitz et al, 1990;Zhang et al, 1994), hypoxia (Long et al, 1997;Sano et al, 2007;Sutton et al, 2008), chemotherapeutic agents (Chuang et al, 2012;el-Deiry et al, 1994;Lowe et al, 1993;Wang et al, 2005) and biomechanical stress (Leri et al, 1998(Leri et al, , 2000Liao et al, 2004). Molecular tools that reveal the activities of p53 would help deepen our understanding of many cellular processes.…”
Section: Introductionmentioning
confidence: 96%